Conserved gene signatures shared among MAPT mutations reveal defects in calcium signaling - Minaya, Miguel A.; Mahali, Sidhartha; Iyer, Abhirami K.; Eteleeb, Abdallah M.; Martinez, Rita; Huang, Guangming; Budde, John; Temple, Sally; Nana, Alissa L.; Seeley, William W.; Spina, Salvatore; Grinberg, Lea T.; et al. (Frontiers in Molecular Biosciences, 2023)
More than 50 mutations in the MAPT gene result in heterogeneous forms of frontotemporal lobar dementia with tau inclusions (FTLD-tau). However, early pathogenic events that lead to disease and the degree to which they are common across MAPT mutations remain poorly understood. The goal of this study is to determine whether there is a common molecular signature of FTLD-tau. To do this, we analyzed genes differentially expressed in induced pluripotent stem cell–derived neurons (iPSC-neurons) that represent the three major categories of MAPT mutations: splicing (IVS10+16), exon 10 (p.P301L), and C-terminal (p.R406W) compared with isogenic controls. The genes that were commonly differentially expressed in MAPT IVS10+16, p.P301L, and p.R406W neurons were enriched in trans-synaptic signaling, neuronal processes, and lysosomal function. Many of these pathways are sensitive to disruptions in calcium homeostasis. One gene, CALB1, was significantly reduced across the three MAPT mutant iPSC-neurons and in a mouse model of tau accumulation. We observed a significant reduction in calcium levels in MAPT mutant neurons compared with isogenic controls, pointing to a functional consequence of this disrupted gene expression. Finally, a subset of genes commonly differentially expressed across MAPT mutations were also dysregulated in brains from MAPT mutation carriers and to a lesser extent in brains from sporadic Alzheimer disease and progressive supranuclear palsy, suggesting that molecular signatures relevant to genetic and sporadic forms of tauopathy are captured in a dish. The results from this study demonstrate that iPSC-neurons capture molecular processes that occur in human brains and can be used to pinpoint common molecular pathways involving synaptic and lysosomal function and neuronal development, which may be regulated by disruptions in calcium homeostasis.